Impact of financial crisis on earnings management in listed companies of Portugal and UK - Kacharava, Aleksandre (2016)
Firm’s financial information is essential to stakeholders’ decision making. Although not always financial statements show the firm’s real image. This study examines listed firms from Portugal and UK. Firms have different purposes to manipulate earnings: some strive for influencing investors’ perception about a particular company, some try to provide better position for gaining finance from credit institutions or paying less tax to tax authorities. Usually, this behaviour is induced when firms have financial problems. Consequently, the study also aims to see the impact of financial crisis on earnings management. We try to answer question how does extent of firms’ involvement in earnings management change when the world undergoes financial crisis. Furthermore, we also compare two countries with different legal forces in terms of quality of accounting to see the main differences. We used a panel data methodology to analyse financial data from 2004 till 2014 of listed firms from Portugal and UK. Beneish (1999) model was applied to categorize manipulator and non-manipulator firms. Analysing accounting information according to Beneish’s ratios, findings suggest that financial crisis had certain impact on firms’ tendency to manipulate financial results in UK although it is not statistically significant. Moreover, besides the differences between Portugal and UK, results contradict the common view of legal systems’ quality, as UK firms tend to apply more accounting techniques for manipulation than the Portuguese ones. Our main results also confirm that some UK firms manipulate ratios of receivables’ days, asset quality index, depreciation index, leverage, sales and general administrative expenses whereas Portuguese firms manipulate only receivables’ days. Finally, we also find that the main reason to manipulate results is not to influence the cost of obtained funds neither to minimize tax burden since net profit does not explain the ratios used in the Beneish model. Results suggest that the main concern to listed firms manipulate results is to influence financial investors perception.